Proceso de atención nutricional en paciente masculino de 76 años de edad con colostomía y mala. - Villalva Álvarez, Víctor Jordán (2022)
According to a study carried out by the WHO in recent years, colon diseases have increased considerably; malabsorption syndrome are pathologies of the digestive system characterized by problems in the absorption of nutrients such as carbohydrates, proteins, lipids, vitamins and minerals. Through the nutritional interventions that were carried out, there were two indicators, the biochemical one where an altered lipid profile was visualized and the dietary one based on a diet low in fiber, rich in saturated fats and insufficient fluid intake; The present case study was proposed, where a nutritional care process was carried out on an adult over 76 years of age who presented a colostomy and malabsorption, through which an assessment of his nutritional status was carried out, including a biochemical, clinical and clinical anthropometric intervention. At the same time, a nutritional intervention plan was carried out to help improve the absorption of nutrients to prevent nutritional deficit problems and malnutrition in the future. A nutritional plan was carried out based on scientific evidence regarding the correct nutritional management of patients undergoing a colostomy, this feeding plan which included a normocaloric diet of soft consistency, hypofat, rich in fiber and liquids to improve the absorption of nutrients, divided into 5 meal times. A follow-up based on the interventions carried out in patients was provided, which there were favorable changes in the level of the interventions carried out, which helped improve malabsorption and signs and symptoms of the disease.